MONTHLY VARIABILITY OF OXIDANT AND ANTIOXIDANT BIOMARKERS OF FRESHWATER CRAYFISH (ASTACUS LEPTODACTYLUS ESCH., 1823) - Barim-Oz, Ozden; Yilmaz, Seval; Sahin, Hulya; Benzer, Fulya (Parlar Scientific Publications (P S P), 2017)
In the present study was determined the effects of monthly variability on enzymatic antioxidant (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px)), antioxidant (reduced glutathione (GSH)) and the oxidant status (nitric oxide (NO), lipid peroxidation (MDA)) in hepatopancreas, muscle, gills and gonad tissues of freshwater crayfish (A. leptodactylus) the monthly collected throughout the year from Keban Dam Lake of Turkey. Results indicate that variations in oxidants and antioxidants with relation to month were not only tissue specific but also were gender specific. The levels of oxidant parameters were generally higher in hepatopancreas in comparison to muscle, gills and gonad of crayfish. Moreover, in tissues were also determined the different oxidants and antioxidants responses in moulting, mating, breeding and egg laying periods.
Keywords: Astacus leptodactylus; year; oxidant; antioxidant; Keban Dam Lake